Combined thalamic and pallidal deep brain stimulation for dystonic tremor. (October 2022) - Trompette, Caroline; Giordana, Caroline; Leplus, Aurélie; Grabli, David; Hubsch, Cécile; Marsé, Claire; Fontaine, Denys
Abstract: Background: Deep brain stimulation (DBS) has been proposed to treat disabling dystonic tremor (DT), but there is debate about the optimal target. DBS of the globus pallidus interna (GPi) may be insufficient to control tremor, and DBS of the ventral intermediate thalamic nucleus (VIM) may inadequately control dystonic features, raising the question of combining both targets. Objectives: To report the respective effects on DT symptoms of high-frequency stimulation of the VIM, the GPi and both targets simultaneously stimulated. Methods: Three patients with DT treated by bilateral high frequency DBS of 2 targets (VIM and GPi) were assessed 12 months after surgery in 4 conditions (VIM and GPi-DBS; GPi-DBS only; VIM-DBS only; DBS switched Off for both targets) by 3 independent movement disorders specialists blinded to the condition. Results: The Fahn-Tolosa-Marin-tremor-rating-scale (FTM-TRS) and Burke-Fahn-Marsden-dystonia-rating-scale (BFM-DRS) scores were more improved by combined DBS than VIM alone or GPi alone. Compared to Off/Off condition, mean total FTM-TRS score decrease was 34%, 42% and 63% respectively with VIM only, GPi only and combined VIM and GPi stimulation. Mean total BFM-DRS score decrease was 34%, 37% and 60% respectively with VIM only, GPi only and combined VIM and GPi stimulation, compared to Off/Off condition. Improvement concerned both motor, functional and activities of daily living sub-scores. No complications or adverse events were observed. Conclusion: Combined VIM- and GPi-DBS, by modulating the cerebello-thalamo-cortical network and the basal ganglia-thalamo-cortical network, both involved in DT pathophysiology, may be more efficient than single DBS targeting only one of them. Highlights: Tremor and dystonia were more improved by combined DBS than VIM or GPi alone. No complication was observed during combined VIM-GPi-DBS, using four leads. VIM-GPi-DBS, modulating both DT networks, may be more efficient than one target.